Neuropsychiatric involvement in juvenile-onset systemic lupus erythematosus: A multicenter study - Kisaarslan, Aysenur Pac; Cicek, Sumeyra Ozdemir; Batu, Ezgi D.; Sahin, Sezgin; Gurgoze, Metin K.; Cetinkaya, Sibel Balci; Dusunsel, Ruhan (Elsevier France-Editions Scientifiques Medicales Elsevier, 2023)
Introduction: Neuropsychiatric (NP) involvement is a restricted area in juvenile-onset systemic lupus erythematosus (jSLE). Aim: To investigate the prevalence, demographic and clinical features, and outcomes of the neurological involvement in the Turkish jSLE population. Methods: This study was based upon 24 referral centers' SLE cohorts, multicenter and multidisciplinary network in Turkey. Patient data were collected by a case report form which was standardized for NP definitions according to American Collage of Rheumatology (ACR). Systemic Lupus International Collab-orating Clinics/American College of Rheumatology Damage Index (SDI) neuropsychiatric part was used to determine NP damage. Variables were evaluated Ward's hierarchical clustering analyses, univariate, and multivariate logistic regression analyses. Results: A hundred forty-nine of 1107 jSLE patients had NP involvement (13.5%). The most common NPSLE findings were headache (50.3%), seizure (38.3%), and acute confusional state (33.6%). Five clusters were identified with all clinical and laboratory findings. The first two clusters involved neuropathies, demyelinating diseases, aseptic meningitis, and movement disorder. Cluster 3 involved headache, activ-ity markers and other SLE involvements. Idiopathic intracranial hypertension, cerebrovascular disease, cognitive dysfunction, psychiatric disorders and SLE antibodies were in the fourth, and acute confusional state was in the fifth cluster. In multivariate analysis, APA positivity; OR: 2.820, (%95CI: 1.002-7.939), P: 0,050, plasmapheresis; OR: 13.804 (%95CI: 2.785-68.432), P: 0,001, SLEDAI scores; OR: 1.115 (%95CI: (1.049-1.186), P: 0,001 were associated with increased risk for neurologic sequelae. Conclusion: We detected the prevalence of juvenile NPSLE manifestations in Turkey. We have identified five clusters that may shed light pathogenesis, treatment and prognosis of NP involvements. We also determined risk factors of neurological sequelae. Our study showed that new definitions NP involvements and sequelae for childhood period are needed. (c) 2023 Socie ' te ' franc,aise de rhumatologie. Published by Elsevier Masson SAS. All rights reserved.
Keywords: Cluster; Juvenile; Systemic lupus erythematosus; Neurologic manifestations